2017
DOI: 10.1186/s12899-017-0032-9
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide high mobility group box-1 causes bladder pain through bladder Toll-like receptor 4

Abstract: BackgroundBladder pain is a prominent symptom in several urological conditions (e.g. infection, painful bladder syndrome/interstitial cystitis, cancer). Understanding the mechanism of bladder pain is important, particularly when the pain is not accompanied by bladder pathology. Stimulation of protease activated receptor 4 (PAR4) in the urothelium results in bladder pain through release of urothelial high mobility group box-1 (HMGB1). HGMB1 has two functionally active redox states (disulfide and all-thiol) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 36 publications
10
31
0
Order By: Relevance
“…A total of 24 h after the first PAR4 instillation, the 50% mechanical threshold was markedly decreased compared with the PAR4 scrambled peptide group (Fig. a; day 1), in agreement with our earlier reports . The mechanical threshold was increased at day 2 before the second intravesical treatment (Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…A total of 24 h after the first PAR4 instillation, the 50% mechanical threshold was markedly decreased compared with the PAR4 scrambled peptide group (Fig. a; day 1), in agreement with our earlier reports . The mechanical threshold was increased at day 2 before the second intravesical treatment (Fig.…”
Section: Resultssupporting
confidence: 91%
“…We recently reported that intravesical PAR4 instillation generated an acute (24 h) bladder pain model where mice showed bladder hypersensitivity without overt bladder inflammation, an important feature, as most IC/BPS patients do not show bladder inflammation . Furthermore, we examined the mechanisms responsible for the development of bladder hypersensitivity, and observed that PAR4 activation led to the release of urothelial MIF and HMGB1 . Both MIF and HMGB1 are necessary for the development of bladder pain in this model and these observations agree with reports showing a role for MIF and HMGB1 in nociception …”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Disulfide (or isomerized) HMGB1, characterized by 2 cysteine residues that are oxidized to form an S-S bond between C23 and C45, was found to induce NF-κB translocation and the secretion of inflammatory factors via TLR-4 in activated immune cells, while mutations of C23 or C45 abrogated the cytokine activity of HMGB1 [14]. It also induced bladder pain via TLR-4 [15]. Frank et al [16] found that it potentiated the neuroinflammatory response in vivo, but that thiol HMGB1 failed to promote the microglial proinflammatory response to lipopolysaccharide (LPS).…”
Section: The Role Of Hmgb1 As a Redox Regulatormentioning
confidence: 99%